2007
DOI: 10.1271/bbb.60711
|View full text |Cite
|
Sign up to set email alerts
|

Novel DPPH Radical Scavengers, Demethylbisorbibutenolide and Trichopyrone, from a Fungus

Abstract: In our screening program for antioxidants with 1,1-diphenyl-2-picrylhydrazyl (DPPH)-radical scavenging activity, two novel compounds, demethylbisorbibutenolide (1) and trichopyrone (2), were isolated from the fermentation broth of the fungus of USF-4860 strain isolated from a soil sample. The structures of these compounds were determined from spectroscopic evidence. The biosynthetic origin of the carbon atoms of 2 was unambiguously determined by feeding experiments using (13)C-labeled precursors and elucidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
(23 reference statements)
1
30
0
Order By: Relevance
“…The mild activity of surugapyrone A is similar to that of the two 4-hydroxy-2-pyrones previously isolated from fungi by our research group. 4,11 Accordingly, the mechanism of the DPPH radical-scavenging of 1 was expected to proceed through formation of an adduct with the DPPH radical. 4,11 Recently, the biosynthesis of similar 2-pyrone derivatives isolated from Streptomyces coelicolor was studied mainly by means of LC/MS analysis.…”
Section: Figure 4 Biosynthetic Origin Of Surugapyrone a (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The mild activity of surugapyrone A is similar to that of the two 4-hydroxy-2-pyrones previously isolated from fungi by our research group. 4,11 Accordingly, the mechanism of the DPPH radical-scavenging of 1 was expected to proceed through formation of an adduct with the DPPH radical. 4,11 Recently, the biosynthesis of similar 2-pyrone derivatives isolated from Streptomyces coelicolor was studied mainly by means of LC/MS analysis.…”
Section: Figure 4 Biosynthetic Origin Of Surugapyrone a (1)mentioning
confidence: 99%
“…4,11 Accordingly, the mechanism of the DPPH radical-scavenging of 1 was expected to proceed through formation of an adduct with the DPPH radical. 4,11 Recently, the biosynthesis of similar 2-pyrone derivatives isolated from Streptomyces coelicolor was studied mainly by means of LC/MS analysis. 12 Our results indicated precise regiospecific incorporation of precursors, suggesting that surugapyrone A (1) was biosynthesized by type III polyketide synthase.…”
Section: Figure 4 Biosynthetic Origin Of Surugapyrone a (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of DPPH radical-scavenging activity. This assay was performed by a previously reported spectroscopic method (Chen et al, 2005;Washida et al, 2007). An MeOH solution (2 mL) of each sample was mixed with a 0.5 mM DPPH MeOH solution (1 mL) in 0.1 M acetate buffer (pH 5.5, 2 mL).…”
Section: Introductionmentioning
confidence: 99%
“…The polarity of the optical rotation values for 1 and 2, both of which were negative, suggests that the stereochemistry of C-6 in 1 is the same as that in 2, an R configuration. Abe et al [6][7][8][9] have reported the isolation of sorbicillin compounds, including oxosorbicillinol (2), from the fungus Trichoderma sp. They also isolated various dimeric compounds and discussed their biosynthetic pathways.…”
mentioning
confidence: 99%